Analysis of Fault Plane and Distribution of Coulomb Stress Changes of the Mw 7.8 Earthquake Southwest of Sumatra - Gabriela Gabriela; Kelly Lasofia Br Girsang; Rizki Wulandari Wulandari; Yudha Styawan (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
The Mw 7.8 earthquake that occurred southwest of Sumatra on March 2, 2016, at a depth of 24 km represents a major seismic event within the Sunda subduction zone, significantly influencing regional stress conditions. This study aims to analyze Coulomb stress changes (Δσc), examine stress distribution patterns, and evaluate the most representative fault plane controlling the earthquake source mechanism. The analysis was conducted using the Coulomb Stress Change method based on focal mechanism parameters and finite fault models obtained from the United States Geological Survey (USGS). The results indicate that Nodal Plane 1 (NP1) represents the true fault plane controlling the earthquake mechanism, with maximum stress increase of up to  0.1 bar and orientations from west–east to northwest–southeast. In contrast, Nodal Plane 2 (NP2) acts as a receiver fault, accommodating transferred stress from the main rupture, with similar stress magnitudes oriented north–south to west–east. The observed stress increases on both nodal planes highlight potential zones for aftershock occurrence. This study contributes to a better understanding of earthquake source mechanisms and stress redistribution patterns that may trigger subsequent seismic activity in the southwest  region of Sumatra..